Magnetic ordering in Cr-doped Bi₂Se₃ thin films - Collins-Mcintyre, LJ; Harrison, SE; Schoenherr, P; Steinke, N-J; Kinane, CJ; Charlton, TR; Alba-Veneroa, D; Phusp, A; Kellock, AJ; Parkin, SSP; Harris, JS; Langridge, S; et al. (European Physical Society, 2014)
We report the structural and magnetic study of Cr-doped Bi2Se3 thin films using x-ray diffraction (XRD), magnetometry and polarized neutron reflectometry (PNR). Epitaxial layers were grown on c-plane sapphire by molecular beam epitaxy in a two-step process. Highresolution XRD shows the exceptionally high crystalline quality of the doped films with no parasitic phases up to a Cr concentration of 12% (in % of the Bi sites occupied by substitutional Cr). The magnetic moment, measured by SQUID magnetometry, was found to be ∼2.1 μB per Cr ion. The magnetic hysteresis curve shows an open loop with a coercive field of ∼10 mT. The ferromagnetic transition temperature was determined to be 8.5 K analyzing the magnetizationtemperature gradient. PNR shows the film to be homogeneously ferromagnetic with no enhanced magnetism near the surface or interface.